2018
DOI: 10.1159/000487504
|View full text |Cite
|
Sign up to set email alerts
|

Dual p16 and Ki-67 Expression in Liquid-Based Cervical Cytological Samples Compared to Pap Cytology Findings, Biopsies, and HPV Testing in Cervical Cancer Screening: A Diagnostic Accuracy Study

Abstract: Objective: Our objective was to verify the sensitivity and specificity of dual immunocytochemistry staining for p16 and Ki-67 in liquid-based samples (the “dual” assay) for cervical lesion screening, compared to biopsy findings and human papillomavirus (HPV) DNA molecular detection. Study Design: Sensitivity, specificity, and positive (PPV) and negative (NPV) predictive values for the “dual immunocytochemistry assay” were calculated and compared to histopathological results and to high-risk HPV DNA detection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The significantly higher specificity of CINtec PLUS than HPV test was consistently observed, and in this respect, we note that CINtec PLUS is currently approved for triaging those testing positive in HPV primary screening [ 29 ]. The lower sensitivity, albeit with the caveats noted, and higher specificity of CINtec PLUS compared to HPV test we observed is consistent with a screening triage study recently reported in a Canadian population [ 23 ] and many other studies [ 17 , 21 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significantly higher specificity of CINtec PLUS than HPV test was consistently observed, and in this respect, we note that CINtec PLUS is currently approved for triaging those testing positive in HPV primary screening [ 29 ]. The lower sensitivity, albeit with the caveats noted, and higher specificity of CINtec PLUS compared to HPV test we observed is consistent with a screening triage study recently reported in a Canadian population [ 23 ] and many other studies [ 17 , 21 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although there are differences in the overall sensitivities and specificities of CINtec PLUS and HPV reported in other studies [ 8 , 23 , 31 , 32 ] it is important to note that our study showed both tests having an identical high level of sensitivity to detect CIN3 , a better clinical predictor of risk and progression to assess test performance, and as such, both can potentially be used for LSIL triage in all age groups [ 10 , 18 , 21 , 33 ]. We also observed high levels of NPV for both CINtec PLUS and HPV tests in all age groups to detect CIN3 as apparent in identical other studies [ 4 , 30 , 32 , 34 ] providing evidence that high grade lesions would be mostly detected in a clinical setting, and reassurance for use of either test for LSIL triage. In this respect we note that the ROC analyses showed no differences in the performance of CINtec PLUS and HPV tests for detection of CIN2 .…”
Section: Discussionsupporting
confidence: 84%
“…p16 is a kind of cyclin kinase inhibitor playing an important role in inhibiting tumorigenesis. In case of deletion, methylation or point mutation of p16 gene, the p16 protein expression level will decline, and the number of abnormal cells will increase, leading to the tumor (16). According to the study of Zhou and Gu (17), the incidence rates of various tumors will be significantly increased after p16-knockout mice are exposed to various carcinogenic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Double labeling is the most-used technique [26][27][28][29][30] and it simultaneously evaluates the overexpression of both P16 INK4a and Ki67, the latter being a marker of cell proliferation. This was demonstrated by Prigenzi et al 25 in their study, in which women with cervical cancer were associated with highrisk HPV infections and were referred for further evaluation in dubious cases such as ASCUS and metaplasia. The study showed the possibility of performing the evaluations separately, as performed in this study; however, it has limited indications 28 .…”
Section: Discussionmentioning
confidence: 87%